Systemic lupus erythematosus in a patient with 22q11.2 deletion syndrome: A case report and review of the literature - Chen Sun; Pingyang Han; Juzhen Yan (Central European Journal of Immunology)
22q11.2 deletion syndrome (MIM: 192430/188400, ORPHA: 567) is the most common chromosomal microdeletion disorder, caused by a hemizygous microdeletion of 2.5 million base pairs on chromosome 22. There is a known association between 22q11.2 deletion syndrome (22q11.2DS), immunodeficiency and autoimmune diseases. However, the co-occurrence of 22q11.2DS and systemic lupus erythematosus (SLE) has been rarely reported. Here, we describe a case of a female teenager with distal type I 22q11.2DS who presented with alopecia, oral ulcers, fever and thrombocytopenia. Laboratory tests showed positive antinuclear antibodies (ANA) and double-stranded DNA (ds-DNA) antibodies, indicative of SLE. Treatment with prednisone, hydroxychloroquine and azathioprine resulted in improvement. We reviewed the literature on the immunological mechanisms involved in 22q11.2DS. Thymic dysplasia, T-cell lymphopenia, and B-cell abnormalities collectively contribute to the immunodeficiency and autoimmune manifestations observed in individuals with 22q11.2DS. Genetic factors such as 22q11.2DS should be considered in the diagnosis of childhood rheumatic diseases. Our case adds to the limited literature on this co-occurrence.